Improving the Reading Comprehension Using Authentic Materials at the Second Grade Students of SMPN 2 Lasusua - Agussalim, Agussalim (USN Kolaka, 2022)
This study aimed to investigate the effect of using authentic materials on students’ reading comprehension. The participants were 26 first-grade students of SMPN 2 Lasusua. The research employed a classroom action research (CAR) design, conducted over two cycles. Data were collected through reading comprehension tests administered at the end of each cycle. The results demonstrated a significant improvement in students’ reading comprehension after the implementation of authentic materials. The average scores increased from 55.12 in Cycle 1 to 71.20 in Cycle 2. Analysis of test results indicated that students showed notable progress particularly in identifying main ideas, suggesting enhanced cognitive engagement and understanding. The findings imply that integrating authentic materials in the reading instruction can effectively enhance students’ comprehension skills and support a more meaningful learning experience. This study provides practical implications for EFL teachers in designing reading activities that promote comprehension and engagement through authentic content